Advanced Data Mining and Applications 19th International Conference, ADMA 2023, Shenyang, China, August 21-23, 2023, Proceedings, Part III - Yang, Xiaochun; Suhartanto, Heru.; Wang, Guoren; Wang, Bin.; Jiang, Jing.; Li, Bing.; Zhu, Huaijie; Cui, Ningning (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes the refereed proceedings of the 19th International Conference on Advanced Data Mining and Applications, ADMA 2023, held in Shenyang, China, during August 21-23, 2023. The 216 full papers included in this book were carefully reviewed and selected from 503 submissions. They were organized in topical sections as follows: Data mining foundations, Grand challenges of data mining, Parallel and distributed data mining algorithms, Mining on data streams, Graph mining and Spatial data mining.
Pharmaceutical Data Analysis -- Drug-target interaction prediction based on drug subgraph fingerprint extraction strategy and subgraph attention mechanism -- Soft Prompt Transfer for Zero-Shot and Few-Shot Learning in EHR Understanding -- Graph Convolution Synthetic Transformer for Chronic Kidney Disease Onset Prediction -- MTFL: Multi-task feature learning with joint correlation structure learning for Alzheimer's disease cognitive performance prediction -- Multi-Level Transformer for Cancer Outcome Prediction in Large-Scale Claims Data -- Individual Functional Network Abnormalities Mapping via Graph Representation-based Neural Architecture Search -- A novel application of a mutual information measure for analysing temporal changes in healthcare network graphs -- Drugs Resistance Analysis from Scarce Health Records via Multi-task Graph Representation -- Text Classification -- ParaNet:Parallel Networks with Pre-trained Models for Text Classification -- Open Text Classification Based on Dynamic Boundary Balance -- A Prompt Tuning Method for Chinese Medical Text Classification -- TabMentor: Detect Errors on Tabular Data with Noisy Labels -- Label-aware Hierarchical Contrastive Domain Adaptation for Cross-network Node Classification -- Semi-supervised classification based on Graph Convolution Encoder Representations from BERT -- Global Balanced Text Classification for Stable Disease Diagnosis -- Graph -- Dominance Maximization in Uncertain Graphs -- LAGCL: Towards Stable and Automated Graph Contrastive Learning -- Discriminative Graph-level Anomaly Detection via Dual-students-teacher Model -- Common-Truss-based Community Search on Multilayer Graphs -- Learning To Predict Shortest Path Distance -- Efficient Regular Path Query Evaluation with Structural Path Constraints.EnSpeciVAT: Enhanced SpeciVAT for Cluster Tendency Identification in Graphs -- Pessimistic Adversarially Regularized Learning for Graph Embedding -- M2HGCL: Multi-Scale Meta-Path Integrated Heterogeneous Graph Contrastive Learning.
Keywords: Data mining; Artificial intelligence; Application software; Computer vision; Education -- Data processing; Computer systems; Data Mining and Knowledge Discovery; Artificial Intelligence; Computer and Information Systems Applications; Computer Vision; Computers and Education; Computer System Implementation